Strategi Kepala Sekolah dalam Mempersiapkan Akreditasi Perpustakaan di SMP Negeri 2 Sangatta Utara - Qatrunnada Jinan Akmaliah; Mukhtar Mukhtar; Muhammad Muhammad (Manajemen Pendidikan Program Doktor, 2026)
Abstract This study aimed to analyze the principal’s strategy in preparing library accreditation at SMP Negeri 2 Sangatta Utara. The study employed a descriptive qualitative approach with data collected through observation, interviews, and documentation. Informants consisted of the principal, head librarian, librarian staff, and accreditation team coordinators. Data were analyzed using the Miles, Huberman, and Saldana interactive model and further examined through SWOT analysis. The findings revealed that the principal’s strategies included optimizing library facilities and infrastructure, improving staff competencies, developing literacy programs and digital services, strengthening collections through external collaboration, improving administrative completeness, prioritizing accreditation standards fulfillment, and conducting periodic evaluations of library readiness. These strategies positioned the library in the Growth Strategy quadrant, indicating favorable conditions for accreditation readiness and continuous improvement of library service quality.